2018
DOI: 10.1021/acs.jproteome.8b00069
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased Proteomic Study of the Axons of Cultured Rat Cortical Neurons

Abstract: The axon is a long projection connecting a neuron to its targets. Here, the axons of cultured rat cortical neurons were isolated with micropatterned chips that enable the separation of axons from their cell bodies. Proteins extracted from isolated axons and whole neurons were subjected to analyses using two-dimensional liquid chromatography-tandem mass spectrometry (2D-LC-MS/MS) analyses without and with stable isotope dimethyl labeling, resulting in the identification of >2500 axonal proteins and 103 axon-enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 69 publications
2
27
0
Order By: Relevance
“…We found that 12.6% (124 of 982) of proteins with these GO terms were detected in our axon sample, some of which were confirmed by immunostaining (Figure 5F). Many of these factors were detected in the axons of different types of neurons, such as mouse callosal axons (Poulopoulos et al., 2019) and axons of rat cortical neurons (Chuang et al., 2018), suggesting that the functions of these factors are conserved among these neuron types (Figure S5G).…”
Section: Resultsmentioning
confidence: 99%
“…We found that 12.6% (124 of 982) of proteins with these GO terms were detected in our axon sample, some of which were confirmed by immunostaining (Figure 5F). Many of these factors were detected in the axons of different types of neurons, such as mouse callosal axons (Poulopoulos et al., 2019) and axons of rat cortical neurons (Chuang et al., 2018), suggesting that the functions of these factors are conserved among these neuron types (Figure S5G).…”
Section: Resultsmentioning
confidence: 99%
“…Irrespective of this, it is enticing to conjecture about an alternative possibility that reflects on the disparity between axonal tctp mRNA and protein expression. Intriguingly, although tctp transcripts have consistently been placed alongside the most abundant in various whole-genome analyses of embryonic and adult axonal transcriptomes (Taylor et al, 2009 ; Andreassi et al, 2010 ; Zivraj et al, 2010 ; Gumy et al, 2011 ), proteomic datasets have not corroborated this notion (Estrada-Bernal et al, 2012 ; Chuang et al, 2018 ), hinting at a non-coding role for tctp mRNAs in axons. As noted in Supplementary Figure S2 and first reported by Clemens and colleagues, tctp transcripts are highly structured and have been shown to bind and activate the double-stranded RNA (dsRNA)-dependent protein kinase PKR (Bommer et al, 2002 ), an intracellular stress sensor upstream of eIF2a, as well as with other physiological roles in signaling (Dabo and Meurs, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study was the first to combine omics analysis at different layers of gene expression, providing data of the local transcriptome, the local translatome, and the local proteome in neurites . The later study identified ≈7000 proteins, and Chang and colleagues analyzed the proteome of cortical axons (Table ), identifying ≈2500 proteins containing constituents of organelles (such as mitochondria, ribosome, endoplasmic reticulum) and cytoskeleton . Finally, the data obtained by the Holt laboratory reveal that approximately one‐third of the axonal proteome is synthesized locally under basal conditions (Table ).…”
Section: Transcriptomic Translatomic and Proteomic Data Of Axons: Kmentioning
confidence: 99%